The UK Pharmacy Care Plan service: Description, recruitment and initial views on a new community pharmacy intervention. - Michael J Twigg; David Wright; Charlotte L Kirkdale; James A Desborough; Tracey Thornley (PLoS ONE, 2017)
INTRODUCTION:The UK government advocates person-centred healthcare which is ideal for supporting patients to make appropriate lifestyle choices and to address non-adherence. The Community Pharmacy Future group, a collaboration between community pharmacy companies and independents in the UK, introduced a person-centred service for patients with multiple long-term conditions in 50 pharmacies in Northern England. OBJECTIVE:Describe the initial findings from the set up and delivery of a novel community pharmacy-based person-centred service. METHOD:Patients over fifty years of age prescribed more than one medicine including at least one for cardiovascular disease or diabetes were enrolled. Medication review and person-centred consultation resulted in agreed health goals and steps towards achieving them. Data were collated and analysed to determine appropriateness of patient recruitment process and quality of outcome data collection. A focus group of seven pharmacists was used to ascertain initial views on the service. RESULTS:Within 3 months of service initiation, 683 patients had baseline clinical data recorded, of which 86.9% were overweight or obese, 53.7% had hypertension and 80.8% had high cardiovascular risk. 544 (77.2%) patients set at least one goal during the first consultation with 120 (22.1%) setting multiple goals. A majority of patients identified their goals as improvement in condition, activity or quality of life. Pharmacists could see the potential patient benefit and the extended role opportunities the service provided. Allowing patients to set their own goals occasionally identified gaps to be addressed in pharmacist knowledge. CONCLUSION:Pharmacists successfully recruited a large number of patients who were appropriate for such a service. Patients were willing to identify goals with the pharmacist, the majority of which, if met, may result in improvements in quality of life. While challenges in delivery were acknowledged, allowing patients to identify their own personalised goals was seen as a positive approach to providing patient services.